Pengaruh Corporate Governance dan Profitabilitas terhadap Penghindaran Pajak dengan Ukuran Perusahaan Sebagai Variabel Pemoderasi - Indira Yuni, Ni Putu Ayu; Setiawan, Putu Ery (E-Jurnal Akuntansi, 2019)
This study aims to determine the effect of corporate governance and profitability on tax avoidance with company size as a moderator. The number of samples analyzed were 55 samples of food and beverage companies listed on the Indonesia Stock Exchange (IDX) in 2013-2017. Determination of samples using purposive sampling technique. Analysis of research data using multiple linear regression and moderation regression analysis. The results of the analysis show that institutional ownership and independent commissioners have a negative influence on tax avoidance. Profitability has a positive effect on tax avoidance. The size of the company strengthens the relationship of institutional ownership with tax avoidance. Company size is not able to moderate independent commissioners with tax avoidance. Company size weakens profitability relations with tax avoidance. Keywords : Tax avoidance; corporate governance; profitability; and company size.